Treatment of hepatitis C in coinfected patients. (December 2015) - Bello, David Del; Ita-Nagy, Fanny; Hand, Jonathan; Dieterich, Douglas
HCV and liver disease have emerged as major causes of morbidity and mortality in HIV-positive patients. Treating HCV in patients with HIV has been challenging up until a few years ago due to poorer outcomes with interferon-based therapies in this population. The direct-acting antiviral (DAA) agents offer a new era in the treatment of HCV for all patients regardless of HIV status. This article reviews multiple aspects of the care of the coinfected patient with a focus on the modern DAA agents. HCV clinical treatment trials involving HIV-positive patients and antiretroviral therapy/DAA drug–drug interactions are reviewed in detail.